New species and records of Oecobius Lucas, 1846 (Araneae: Oecobiidae) from Iran and Azerbaijan - Zamani Alireza; Marusik Yuri M. (Taylor & Francis, 2025)
New data on the oecobiid spiders of the genus Oecobius Lucas, 1846 occurring in Iran and Azerbaijan are provided. Five species are described as new to science: O. dariusi sp. n. (♀; Alborz and Tehran ‒ northern Iran), O. melanocephalus sp. n. (♀; Lorestan, Razavi Khorasan, Semnan, and Tehran ‒ south-western, northern and north-eastern Iran; hitherto described as the female of O. ferdowsii Mirshamsi, Zamani and Marusik, 2017), O. naxuanus sp. n. (♂; Nakhchivan ‒ western Azerbaijan), O. pasargadae sp. n. (♂♀; Fars ‒ south-central Iran), and O. zagros sp. n. (♂; Kermanshah ‒ western Iran). Furthermore, O. navus Blackwall, 1859 is reported in Iran for the first time, and new distribution records are provided for O. putus O. Pickard-Cambridge, 1876 and O. nadiae (Spassky, 1936).